2000
DOI: 10.2165/00128071-200001060-00005
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Placebo-Controlled Trial of Topical Retinol in the Treatment of Cellulite

Abstract: We hypothesize that the functional and phenotypic changes seen in this study were linked and represent the result of a direct or indirect modulating effect of retinol on cellulite. Such features ultimately improve the resting tensions inside the skin which should in turn smooth the skin surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 24 publications
0
29
0
2
Order By: Relevance
“…At the latter sites, edema and deposits of proteoglycans may be present in association with alterations in the shape and pattern of distribution of the elastic fibers 4,7 . Such histological changes found in the hypodermis of cellulite are reminiscent of the dermal changes found in striae distensae 4,7,12 …”
Section: Skin Structure Alterations In Cellulitementioning
confidence: 99%
See 1 more Smart Citation
“…At the latter sites, edema and deposits of proteoglycans may be present in association with alterations in the shape and pattern of distribution of the elastic fibers 4,7 . Such histological changes found in the hypodermis of cellulite are reminiscent of the dermal changes found in striae distensae 4,7,12 …”
Section: Skin Structure Alterations In Cellulitementioning
confidence: 99%
“…Histological studies of cellulite are few but contradictory 4–7,10–12 . Globally, we view cellulite as the result of a combination of the gender‐related dimorphism of the hypodermal connective tissue and the mechanobiological effects of tissue tensions inside this tissue 4 .…”
Section: Skin Structure Alterations In Cellulitementioning
confidence: 99%
“…Moreover, a mixture of retinol, caffeine, and ruscogenin was able to reduce the orange-peel appearance and increase microcirculation in a clinical study reported by Bertin et al19 Single ingredients, also found in this formulation have documented anti-cellulite activity as well. This is the case for retinol, which by itself, improves skin thickness in patients with cellulite, as demonstrated clinically by Kligman et al,20 while Piérard-Franchimont et al21 reported effects on tensile properties of skin, in the context of cellulite. Acting to strengthen capillaries and limit edema when applied topically, escin, derived from horse chestnut, is another ingredient of the current gel that has found application in anti-cellulite formulations 22,23…”
Section: Introductionmentioning
confidence: 76%
“…14 RCTs [18][19][20][21][22][23][24][25][26][27][28][29][30][31], eine Metanalyse inklusive systematischem Review [32] und 2 Beobachtungsstudien [33,34] ohne schließende Statistik wurden bereits verö entlicht. Insgesamt wurden 600 Patienten in diesen klinischen Studien untersucht, die meistens Kombinationsprodukte mit Ko ein und/oder Retinol in Kombination mit p anzlichen Inhaltssto en verwendeten.…”
Section: Topische Wirkstoffeunclassified